A STUDY ON DIGITAL MARKETING - T, Boomika Imayavarthini. (International Journal of Psychosocial Rehabilitation, 2020)
Digital marketing is ascending in India at a quick pace. Numerous Indian organizations are utilizing computerized advertising for upper hand. Accomplishment of promoting effort can't be exclusively accomplished by advanced advertising as it were. Or maybe for accomplishment of any promoting effort it ought to completely saddle the abilities of different advertising strategies accessible inside both the customary and current showcasing. New businesses who utilize computerized advertising commonly got fizzled. This investigation demonstrates precautionary measures to be taken for successful execution of computerized advertising to harvest huge potential to increment in deals.The study found out that Descriptive research onDigital Marketing .convenient sampling method is used in this study to collect the sample.58 samples are recorded .The independent variables used are ,Marital status,age.The dependent variables digital Marketing,digital marketing playing major role..The statistics used is chi-square.Keywords-